Implementation Of Accounting Information System For Inventory Of Medicines At Anuntaloko Parigi Regional General Hospital - Carolina, Si Putu Kezya; Ansar, Muhammad (ISAS, 2025)
This study aims to explore the application of accounting information systems in the management of medicine inventory at Anuntaloko Parigi Hospital. The transformation from a manual Excel-based system to an integrated system using the Mirsa application is an important point in an effort to improve the efficiency and accuracy of recording and reporting. This research uses a qualitative method with a phenomenological approach to explore the direct experiences of hospital employees, such as the pharmacy and finance departments. The results showed that the implementation of the accounting information system has improved recording efficiency, structured the procurement process, and provided a correction mechanism for recording errors. Technical constraints such as network disruptions and initial adaptation processes were overcome through training and infrastructure improvements. In addition, internal and external audits have strengthened accountability and system sustainability. This study confirms that the successful implementation of accounting information systems is not only determined by technology, but also by the readiness of human resources and coordination between work units in the hospital.